The Drosophila U7 snRNP proteins Lsm10 and Lsm11 are required for histone pre-mRNA processing and play an essential role in development. - Godfrey, A.C.; White, A.E.; Tatomer, D.C.; Marzluff, W.F.; Duronio, R.J. (RNA (New York, N.Y.), 2009)
Metazoan replication-dependent histone mRNAs are not polyadenylated, and instead terminate in a conserved stem-loop structure generated by an endonucleolytic cleavage of the pre-mRNA involving U7 snRNP. U7 snRNP contains two like-Sm proteins, Lsm10 and Lsm11, which replace SmD1 and SmD2 in the canonical heptameric Sm protein ring that binds spliceosomal snRNAs. Here we show that mutations in either the Drosophila Lsm10 or the Lsm11 gene disrupt normal histone pre-mRNA processing, resulting in production of poly(A)+ histone mRNA as a result of transcriptional read-through to cryptic polyadenylation sites present downstream from each histone gene. This molecular phenotype is indistinguishable from that which we previously described for mutations in U7 snRNA. Lsm10 protein fails to accumulate in Lsm11 mutants, suggesting that a pool of Lsm10-Lsm11 dimers provides precursors for U7 snRNP assembly. Unexpectedly, U7 snRNA was detected in Lsm11 and Lsm1 mutants and could be precipitated with anti-trimethylguanosine antibodies, suggesting that it assembles into a snRNP particle in the absence of Lsm10 and Lsm11. However, this U7 snRNA could not be detected at the histone locus body, suggesting that Lsm10 and Lsm11 are necessary for U7 snRNP localization. In contrast to U7 snRNA null mutants, which are viable, Lsm10 and Lsm11 mutants do not survive to adulthood. Because we cannot detect differences in the histone mRNA phenotype between Lsm10 or Lsm11 and U7 mutants, we propose that the different terminal developmental phenotypes result from the participation of Lsm10 and Lsm11 in an essential function that is distinct from histone pre-mRNA processing and that is independent of U7 snRNA.